Modular fuzzy control with input shaping technique for transformation of two-wheeled wheelchair to four-wheeled mode - Ahmad, Salmiah; Tokhi, M. Osman; Siddique, Nazmul Haque (IEEE, 2010)
This paper presents a mechanism for wheelchair transformation from two-wheeled upright position to four-wheeled position using a modular fuzzy logic control (MFC) approach. A wheelchair model that can be operated in four-wheeled and two-wheeled modes has been developed within the Visual Nastran environment and integrated with Simulink for control purposes. A multi-input multi-output modular fuzzy logic control configuration is designed and implemented on the wheelchair model. To improve the system performance, an input shaping technique is augmented inside the feedback loop. It is shown that the shaped signals have improved the system performance with promising results.